Going mobile: Non‐cell‐autonomous small RNAs shape the genetic landscape of plants. Issue 3 (10th March 2015) - Pyott, Douglas E.; Molnar, Attila
Summary RNA silencing is a form of genetic regulation, which is conserved across eukaryotes and has wide ranging biological functions. Recently, there has been a growing appreciation for the importance of mobility in RNA silencing pathways, particularly in plants. Moreover, in addition to the importance for mobile RNA silencing in an evolutionary context, the potential for utilizing mobile short silencing RNAs in biotechnological applications is becoming apparent. This review aims to set current knowledge of this topic in a historical context and provides examples to illustrate the importance of mobile RNA silencing in both natural and artificially engineered systems in plants.